Editorial - Paul Puschmann; Joana Maria Pujadas-Mora; Eva van der Heijden (Historical Life Course Studies)
In this new editorial of Historical Life Course Studies key shifts are discussed. We welcome Joana Maria Pujadas-Mora as new co-editor in chief and Eva van der Heijden as associate editor. We thank Luciana Quaranta for her contributions to the development of the journal. Over the past years, Historical Life Course Studies has experienced substantial growth in terms of output and impact. The journal got indexed in Scopus and an application for admission to the Web of Science is pending. Social media engagement and upcoming video releases further enhance the journal's outreach. Gratitude extends to sponsors for Diamond Open Access support, as well as to all authors, reviewers, and readers who jointly contribute to the success of Historical Life Course Studies. The editors look with confidence to the future and hope to welcome many submissions over the next years.